KEBIJAKAN POTONGAN HARGA DAN VOLUME PENJUALAN - DESI KRISTANTI (STIE Indonesia Malang, 2018)
Every company wants a position or position that is more profitable and can survive and earn profits accordingly. Price discount policy is a matter of interest to the consumer and can increase the sales volume. Because in the provision of a very large discount the effect on the increase of sales volume, then the company must be able to establish the right price cut policy to meet the desired sales target inmaximizing corporate goals. Price discount policy is one of the driving factors to increase sales volume.This study aims to: know how the effect of discounted policy on sales volume. From result of research can be concluded that:1) From the calculation of correlation analysis done to produce correlation coefficient value of 0.963 which means that between the policy discount (X) with sales volume (Y) has a strong or positive relationship; 2) From the results of regression analysis obtained regression equation Y = 213 + 5.8X. So if the discount policy is increased by one part (1 part) then the sales volume will increase by 5.8 units. Suggestions that writers can give to the company are: The company should pay more attention to the policy of price discount, in order to increase company sales volume. This is very important because with the increase in sales volume indirectly sales results in the company also increasedKeywords: Price discount policy, and sales volume.